2006
DOI: 10.1534/genetics.106.064956
|View full text |Cite
|
Sign up to set email alerts
|

dSno Facilitates Baboon Signaling in the Drosophila Brain by Switching the Affinity of Medea Away From Mad and Toward dSmad2

Abstract: A screen for modifiers of Dpp adult phenotypes led to the identification of the Drosophila homolog of the Sno oncogene (dSno). The dSno locus is large, transcriptionally complex and contains a recent retrotransposon insertion that may be essential for dSno function, an intriguing possibility from the perspective of developmental evolution. dSno is highly transcribed in the embryonic central nervous system and transcripts are most abundant in third instar larvae. dSno mutant larvae have proliferation defects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 48 publications
7
67
0
Order By: Relevance
“…Alternatively, Sno proteins in M. musculus, D. melanogaster and C. elegans have been shown to facilitate TGFb signaling. For example, in D. melanogaster, the dSno (SnooFlyBase) mutant phenotype mimics the loss of Activin signaling, and biochemical studies have revealed that dSno facilitates Activin signaling by shifting the affinity of the Co-Smad Medea away from Mad (the BMP-dedicated R-Smad) and towards dSmad2 (Smox -FlyBase) (Takaesu et al, 2006). Taken together, these data suggest that the influence of Sno proteins on TGFb signaling is probably tissue specific.…”
Section: Tgfb Signal Transduction Pathwaysmentioning
confidence: 88%
“…Alternatively, Sno proteins in M. musculus, D. melanogaster and C. elegans have been shown to facilitate TGFb signaling. For example, in D. melanogaster, the dSno (SnooFlyBase) mutant phenotype mimics the loss of Activin signaling, and biochemical studies have revealed that dSno facilitates Activin signaling by shifting the affinity of the Co-Smad Medea away from Mad (the BMP-dedicated R-Smad) and towards dSmad2 (Smox -FlyBase) (Takaesu et al, 2006). Taken together, these data suggest that the influence of Sno proteins on TGFb signaling is probably tissue specific.…”
Section: Tgfb Signal Transduction Pathwaysmentioning
confidence: 88%
“…This cDNA closely resembles dSnoI as described by Takaesu et al (Takaesu et al, 2006). The 1360 bp amplified fragment was cloned in pCR-TOPO 2.1 and sequenced.…”
Section: Cloning Of Drosophila Sno (Dsno)mentioning
confidence: 96%
“…In particular, we characterized the ovarian function of the Drosophila homolog of the Sno oncogene. dSno has recently been shown to antagonize TGF-␤ signaling in nervous system and in wing development (Takaesu et al, 2006;Ramel et al, 2007).…”
Section: The Functions Of Dsno and Brinker In Dorsal Follicle Cell Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Stage of lethality tests were as described (Takaesu et al, 2006). Alignments and phylogenetic trees were as described previously (Konikoff et al, 2010).…”
Section: Geneticsmentioning
confidence: 99%